Windbreak Efficiency in Agricultural Landscape of the Central Europe: Multiple Approaches to Wind Erosion Control - Vacek, Zdeněk; Řeháček, David; Cukor, Jan; Vacek, Stanislav; Khel, Tomáš; Sharma, Ram P; Kučera, Josef; Král, Jan; Papaj, Vladimír (Environmental management, 2018)
Windbreak is one of the key factors for making the agriculture systems successful through reduced wind erosion, improved microclimate, increased biodiversity, and production potentiality of timber and agricultural crops. Even though windbreak occupies only a small part of agricultural landscape, its advantages on the ecological and economical perspective are quite high. This study evaluated the effects of three windbreak types on the wind erosion control in relation to their structural diversities, wind-speed reduction, and optical porosities in the central part of the Czech Republic. Diversity in the windbreak was evaluated based on its species diversity, vertical structure, spatial pattern, and complexities. Wind speed was measured at the different distances on the leeward side of the windbreak and one station placed on the windward side as a control. Windbreak characteristics were described by terrestrial photogrammetry method using the values of optical porosity. The timber volume of the windbreaks with rich biodiversity species ranged from 224 to 443 m3 ha-1height of the windbreak on the. Results of the windbreak efficiency showed significantly closer relationship between optical porosity and structural indices. The optical porosity significantly correlated with wind-speed reduction, especially in the lower part of the windbreak. A significant dependency of the windbreak efficiency on the tree dominant height was also observed for each windbreak type. The most significant effect on the wind-speed reduction in terms of structural indices had total diversity index and Arten-profile index describing vertical structures, which are recommended together with the optical porosity to evaluate the windbreak efficiency in controlling wind erosion.
Keywords: ekologie; zachování přírodních zdrojů; stromy; Wind; Ecology; Wind-speed reduction; Europe; Optical porosity; vítr; Evropa; Trees; Structural diversity; Conservation of Natural Resources; Czech Republic; Airflow; Production; zemědělství; Agriculture